2013
DOI: 10.1093/infdis/jit322
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Induced Gag-Specific T Cells Are Associated With Reduced Viremia After HIV-1 Infection

Abstract: The contribution of host T-cell immunity and HLA class I alleles to the control of human immunodeficiency virus (HIV-1) replication in natural infection is widely recognized. We assessed whether vaccine-induced T-cell immunity, or expression of certain HLA alleles, impacted HIV-1 control after infection in the Step MRKAd5/HIV-1 gag/pol/nef study. Vaccine-induced T cells were associated with reduced plasma viremia, with subjects targeting ≥3 gag peptides presenting with half-log lower mean viral loads than subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 47 publications
8
65
1
Order By: Relevance
“…Our findings that Gag p24-and Nef-specific CD8 ϩ T cells are most associated with HIV-1 inhibition agree with previous research (63)(64)(65)(66)(67). We previously demonstrated that Gag-and Nefdominant soluble activity mediated by CD8 ϩ T cells during acute HIV-1 infection corresponded to the breadth of virus inhibition, as well as immune pressure against transmitted founder viruses, but that this activity was diminished by 6 months postinfection in the patients examined (6).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings that Gag p24-and Nef-specific CD8 ϩ T cells are most associated with HIV-1 inhibition agree with previous research (63)(64)(65)(66)(67). We previously demonstrated that Gag-and Nefdominant soluble activity mediated by CD8 ϩ T cells during acute HIV-1 infection corresponded to the breadth of virus inhibition, as well as immune pressure against transmitted founder viruses, but that this activity was diminished by 6 months postinfection in the patients examined (6).…”
Section: Discussionsupporting
confidence: 92%
“…All SPs were antiretroviral therapy naive during the study period, and no TPs were on therapy at the time point analyzed. HLA typing was performed using sequence-based typing as previously described (35).…”
Section: Methodsmentioning
confidence: 99%
“…Antibody measurements were acquired on a Bio-Plex instrument (Bio-Rad), and Taken together, the HVTN 078 data provide support for further characterization of heterologous vector combinations in clinical trials. A high dose of a priming adenovirus vector followed by a poxvirus vector would be a preferred regimen based on our data, as increased nAb titers may provide additional benefit in preventing HIV infection in people compared with the NHP model, and stronger cellular immune responses can provide a second line of defense to contain virus replication should breakthrough infection occur (31). Moving forward, adenovirus vectors of low seroprevalence, such as Ad26 or Ad35, or nonhuman adenovirus vectors based on chimpanzee-or gorilla-derived adenoviruses should replace the rAd5 vector used in this trial; alternatively, other heterologous immunogens, such as DNA, could replace the adenovirus prime.…”
Section: Functionality Of Responses Is Similar Across All Tested Regimentioning
confidence: 99%
“…Although cellular responses may not primarily have an effect on HIV acquisition, data from NHP studies as well as from the Step Study show that increased vaccine-induced Gag-specific T cell responses are associated with a reduced viral load set-point (20,31). Along with responses to the other proteins contained in the HVTN 078 vaccines, we found that Gag-specific CD4 + and CD8 + T cell responses were more frequent and of higher magnitude in the NYVAC-B-boosted groups.…”
Section: Functionality Of Responses Is Similar Across All Tested Regimentioning
confidence: 99%